Age, courtship and senescence: sexual ornaments are larger in older great crested newts. (21st June 2018) - Palau Daval, N.; Gardette, V.; Joly, P.
Abstract: Patterns of senescence are highly diverse and the underlying mechanisms are controversial. Most studies have focused on endothermic tetrapods, who usually exhibit both actuarial (e.g. the increase in mortality rate with age) and reproductive senescence. However, senescence patterns are less clear in ectothermic vertebrates since these animals exhibit undetermined growth and often increase their reproductive potential throughout their life history. We contribute to this topic by investigating the relationship between age and relative size of sexual ornaments in a urodele amphibian, the great crested newt, Triturus cristatus . We found that the relative sizes of sexual ornaments (crest height, crest area, area of the white caudal spot) were correlated with an individual's age in a population monitored in the wild. These sexual ornaments constitute honest signals reflecting male quality. Thus, the crested newt appeared to undergo negligible reproductive senescence in our population, although further experiments on reproductive success are needed to confirm this hypothesis. Abstract : Senescence patterns are unclear in ectothermic vertebrates and we contribute to this topic by investigating the relationship between age and relative size of sexual ornaments in a urodele amphibian, the great crested newt, Triturus cristatus. We found that the relative sizes of sexual ornaments (crest height, crest area, area of the white caudal spot) were correlated with an individual's age. While these sexual ornaments constitute honest signals reflecting male quality, we assume that the older the male, the more likely it is to be selected by females who apply a strong selection pressure by means of a complex courtship display.